SUSTAINABILITY ANALYSIS OF MICROHYDRO POWER PLANTS IN JAYAPURA REGENCY, PAPUA - Adhitia, Pius; Sulaiman, Muhammad; Budiarto, Rachmawan (Master in Systems Engineering, 2022)
The need for energy and electricity in a number of regions currently tends to increase every year. The fast pace of modernization and increasing economic activity in various parts of Indonesia are the main factors triggering the increase in energy demand. The data analysis technique in this study was using quantitative correlation methods with questionnaires and data from field observations. Data in the form of questionnaires and data from observations are primary data in this study. The purpose of this survey is to measure the performance of Micro hydro Power Plants (MHPP) at each site using KPIs related to the sustainability of the site. In addition to verifying objects that are connected and not connected to the MHPP, this survey also covers topics related to the sustainability of the MHPP site which includes operational status, finances, checking of physical components and the results obtained. Based on a survey conducted on the five MHPP sites, there are 325 houses stairs, 24 social institutions, and 28 PUE, Non-functioning buildings are the main reason, Damage to components and the presence of new generators are the main reasons behind MHPP not operating, There is a correlation between MHPP performance and customer satisfaction, Tariff system applied by all MHPP sites is a fixed rate with a cost of Rp. 20,000.00 to Rp. 30,000.00, All MHPP sites, Damage to generator and ELC components, Deforestation occurs in all MHPP sites, and Based on physical checks on MHPP.